Effects of blood flow restriction combined with high-load training on muscle strength and sports performance in athletes: a systematic review and meta-analysis - Su, Chentianlei; Zhang, Zhenglong; Liang, Bin; Zhou, Sicen; Long, Xingyu (Frontiers in Physiology, 2025)
ObjectiveThis study aims to present updated convergent analyses and data following systematic review and meta-analysis protocols to determine the effects of high-load resistance training (HL-RT) combined with blood flow restriction (BFR) on athletes’ physiological adaptations (muscle strength and body composition) and athletic performance (power, speed, and endurance).MethodsA systematic literature search was conducted using Boolean operators with keyword combinations in PubMed, Web of Science, and Embase for studies published up to February 2025. Methodological quality was assessed via the Cochrane Risk of Bias tool. Heterogeneity testing, data synthesis, subgroup analyses, forest plot generation, and sensitivity analyses were performed using RevMan 5.4 and STATA 17.0. Funnel plots were constructed to assess publication bias, while subgroup and regression analyses were employed to identify moderators.ResultsAmong the 887 articles identified through the systematic search process, 10 studies met the inclusion criteria, with a total of 93 athletes completing HL-BFRT and 91 athletes completing HL-RT interventions. Our results showed significant improvements in athletes’ muscle strength (SMD = 0.65, I2 = 44%), power (SMD = 0.45, I2 = 0%), speed (SMD = 0.78, I2 = 60%), and endurance (SMD = 0.90, I2 = 51%) after HL-BFRT interventions, whereas no significant effect was observed on body composition (p > 0.05). Subgroup analyses revealed differential effects of HL-BFRT under various moderators: For muscle strength, significant improvements were observed in both isokinetic tests (SMD = 0.78, p = 0.02) and 1RM tests (SMD = 0.69, p < 0.001), though heterogeneity was higher in the isokinetic subgroup (I2 = 57%). Short-term interventions (≤6 weeks, SMD = 0.80) had significantly greater effect sizes compared to long-term interventions (>6 weeks, SMD = 0.50), and higher training frequency (≥3 sessions/week, SMD = 0.92) was superior to lower frequency (<3 sessions/week, SMD = 0.33), with subgroup heterogeneity approaching significance (I2 = 72%, p = 0.06). There was no significant heterogeneity between the absolute pressure group (SMD = 0.75) and the individualized pressure group (SMD = 0.62), as indicated by I2 = 0%. This reflects similarity in effect sizes across subgroups, rather than a statistical comparison between them. Improvements in power were significant only in short-term interventions (≤6 weeks, SMD = 0.62), whereas long-term interventions were ineffective (SMD = 0.07). Absolute pressure (SMD = 0.52) showed potentially greater benefits than individualized pressure (SMD = 0.39). Speed improvements were observed only with absolute pressure (SMD = 1.38, p = 0.003), and endurance improvements approached significance under absolute pressure (SMD = 1.29, p = 0.06), with no significant effect under individualized pressure conditions. All subgroups exhibited low heterogeneity (I2 = 0–32%).ConclusionThis meta-analysis indicates that HL-BFRT may serve as an effective alternative to traditional HL-RT, showing potential advantages in improving athletes’ muscle strength, power, speed, and endurance performance. Short-term, high-frequency interventions (≤6 weeks, ≥3 sessions/week) using absolute pressure appear optimal for performance enhancement, while individualized pressure protocols may better balance safety and effectiveness in clinical settings.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025636274, identifier [CRD42025636274 (PROSPERO)].